A new deep-sea species of Halirages Boeck, 1871 (Crustacea: Amphipoda: Calliopiidae) inhabiting sponges - Lörz, Anne-Nina; Nack, Madita; Tandberg, Anne Helene S.; Brix, Saskia; Schwentner, Martin (European Journal of Taxonomy, 2024)
In the vast abyssal plains northwest of Iceland, white glass sponges of the genus Caulophacus Schulze, 1886 were inhabited by reddish Bythocaris G.O. Sars, 1870 shrimps and pinkish amphipods. After in situ observations at 3700 m depth, in -1°C waters by a remotely operated vehicle, members of this assemblage were collected and preserved for molecular studies. Based on integrative taxonomic analyses, the amphipods were identified as a new species of the genus Halirages Boeck, 1871 – Halirages spongiae sp. nov. Lörz, Nack & Tandberg –, as described in detail below. Part of our integrative approach was to establish reference DNA barcodes for known species of Halirages. However, our investigation of material of Calliopiidae G.O. Sars, 1895 collected around Iceland and Norway revealed slight morphological discrepancies in all the described species of Halirages. Except for Halirages fulvocinctus (M. Sars, 1858), none of the encountered specimens of Calliopiidae fully matched a current species description. We illuminate the morphological characteristics of nine operational taxonomic units, which also represented clades in COI and 28S. We set the Icelandic samples in the context of Halirages from Canada and Norway. A key to the world species of Halirages is provided.